Analisis Kualitas Layanan Pada Badan Pengelolaan Keuangan Dan Aset Daerah Kota Sorong Provinsi Papua Barat - Kondologit, Aryanti Sopia (JURNAL RISET BISNIS DAN MANAJEMEN, 2014)
The aims of this study is to study service quality in the Badan Pengelolaan Keuangan dan Aset Daerah (BPKAD) sorong City based on the aspects of reliability, emphaty, responsiveness, assurance and tangible. The result show that reliability, emphaty, responsiveness, assurance and tangible have a significanty effect to the customer satisfaction, simultaneous and partially. Keywords: Service Quality, Customer Satisfaction